The precision of radiographic and electronic working length estimation methods in endodontics: A systematic review of clinical studies - Anithakumari Rangappa; Buvaneshwari Arul; Jayalakshmi Somasundaram; Velmurugan Natanasabapathy (Endodontology)
Aim: This study aimed to review the literature to know the precision of electronic apex locators over the radiographic method in the estimation of working length (WL) from the clinical studies. Methods: The research question was framed in PICO format; the study protocol was registered in PROSPERO and the systematic search was done following Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The literature search was accomplished in PubMed, Scopus, Cochrane, and Google Scholar databases until February 29, 2023, for articles in the English language. Results: A total of 2332 articles were obtained after the initial search. Three hundred and ten duplicates and 1295 articles not meeting the eligibility criteria were removed before screening. Two hundred and fifteen records were screened and 181 articles were included after reading the abstract and title. After the application of the inclusion and exclusion criteria, five studies were included in the review. The assessment of the quality of the selected articles was done using a revised tool for the quality assessment of diagnostic accuracy studies-2. Conclusion: It is inconclusive about the precision of radiographic and electronic methods in WL estimation since the studies included are at high risk of bias, hence electronic method verified radiographically could be the recommended WL estimation protocol.